Identifikasi tingkat perkembangan remaja siswa SMA di kota Singkawang pada aspek landasan hidup religius - Iip Istirahayu; Dian Mayasari (Seminar Nasional Bimbingan dan Konseling Jambore Konseling 3)
Every Man has always been progressing in a phase of life. Disturbance at one stage will hinder the development as a whole. The purpose this research is to identify the level of development of adolescents of high school students in Singkawang on a foundation of religious life aspect. This research is a quantitative inferential. The study was conducted on the 12 SMA in Singkawang. Data collection technique is using the Inventory Task Progress (ITP). Data were analyzed using Task Analysis Progress (ATP) with the adoption of the categories in the Encoding level of development. The results showed that the development of adolescent high school students in Singkawang on the runway area religious life is one school located at saksama level and 〖11〗^th schools at the level of individuality.